Self-Actualization and Anxiety in Early Adult Female Victims of Domestic Violence During Childhood - Fadhilah Umaira Alfahis; Naomi Soetikno (Philanthropy: Journal of Psychology, 2023)
Domestic violence (DV) is one of the forms of violence that affects not only adults but also children. Experiencing or witnessing DV in childhood can have long-term psychological impacts, such as the development of an anxious personality in adulthood. As individuals grow, they need to fulfill specific needs to achieve self-actualization, including safety needs. Individuals with high anxiety are most likely to have a threatened sense of security. Thus, the anxiety is predicted to be related to self-actualization. This research aims to investigate the relationship between self-actualization and anxiety in adult women who were victims of DV during childhood, with a total of 240 early adult women. The data analysis method is quantitative correlational. The findings revealed a correlation coefficient of -0.523 with a significance value of 0.000 (p < 0.05), indicating a negative correlation between self-actualization and anxiety in early adult women who experienced DV during childhood.Keywords: Anxiety, Self-Actualization, Domestic Violence